Possibilities of magnetic resonance imaging in predicting of the critical reduction of left ventricle contractile function in patients with coronary artery disease after direct myocardial revascularization - N. A. Kryukov; A. V. Ryzhkov; I. V. Sukhova; P. V. Ananyevskaya; V. A. Fokin; M. L. Gordeev (Российский кардиологический журнал, 2019)
Aim. To identify the criteria for reversibility of structural changes in the myocardium of patients with coronary artery disease after revascularization based on analysis of data obtained using magnetic resonance imaging (MRI).Materials and methods. We studied the long-term results of surgical treatment of 53 patients with critical reduction of left ventricle contractile function (ejection fraction less than 30%) undergoing coronary bypass surgery. Before the operation, all patients underwent cardiac MRI and transthoracic echocardiography (EchoCG). Immediate and long-term results were assessed according to EchoCG.Results. The average observation period was 25,0±15,4 months. We found that significant predictors of improving of left ventricle contractile function are diastolic interventricular septum thickness (according to EchoCG and MRI) >10,5 mm (p<0,05); diastolic posterior wall thickness (according to EchoCG and MRI) >9,5 mm (p<0,05); degree of initially scarred myocardium according to MRI <33 points (p<0,05).Conclusion. Detection of a viable myocardium is a prognostically important sign of a possible improvement in the functional state of left ventricle after revascularization surgery in patients with coronary artery disease, complicated by a critical reduction of myocardium contractile function. Thus, this problem can be solved by contrasting MRI.